A influência da Organização Internacional do Trabalho (OIT) na definição dos padrões normativos no Brasil - Ervolino, Ivan (Universidade Federal de São Carlos, 2011)
This research examines the ability to normative creation of the International Labour Organization (ILO). Previous surveys had indicated that the ILO had participation in public debate on labour issues in Brazil. Objectives: To evaluate the importance of the ILO in standardization of labour issues. Method: The research relies on the available documentation (NATLEX and ILOLEX) and the national and international literature about ILO. Results: The research showed two Features: 1) The ILO project has changed very little due to its institutional design that gives the organization the flexibility to act in different contexts of different times. 2) The ILO has a capacity required to guide decisions of actors and even set new agendas in Brazil.
Keywords: Instituições políticas; Desempenho institucional; Criação normativa; Teoria das Instituições; Organização Internacional do Trabalho; Theory of Institutions; International Labour Organization; Creation Normative; CIENCIAS HUMANAS::CIENCIA POLITICA